Bundle management strategy in reducing hospital-acquired pneumonia in hospitalized patients with mental disorders - Han, Jingjing; Li, Dan; Rao, Yan; Wang, Gaohua (Frontiers in Psychiatry, 2023)
Introduction The incidence of hospital-acquired pneumonia (HAP) is high in the medical setting for mental disorders. To date, effective measurements for preventing HAP in hospitalized mental disorder patients are unavailable. Methods This study was conducted at the Large-Scale Mental Health Center of Renmin Hospital of Wuhan University (Wuhan, China) in two phases: baseline phase (January 2017–December 2019) and intervention phase (May 2020–April 2022). In the intervention phase, the HAP bundle management strategy was implemented in the Mental Health Center, and the data on HAP were collected continuously for analysis. Results A total of 18,795 and 9,618 patients were included in the baseline and intervention phases, respectively. The age, gender, ward admitted to, type of mental disorder, and Charlson comorbidity index did not differ significantly. After intervention, the rate of HAP occurrence decreased from 0.95 to 0.52% (P < 0.001). Specifically, the HAP rate decreased from 1.70 to 0.95% (P = 0.007) in the closed ward and from 0.63 to 0.35% (P = 0.009) in the open ward. The HAP rate in the subgroups was higher in patients with schizophrenia spectrum disorders (1.66 vs. 0.74%) and organic mental disorders (4.92 vs. 1.41%), and in those ≥65 years old (2.82 vs. 1.11%) but decreased significantly after intervention (all P < 0.05). Conclusion The implementation of the HAP bundle management strategy reduced the occurrence of HAP in hospitalized patients with mental disorders.